Check And Balance Dalam Sistem Pemerintahan Indonesia - Adi Syaputra Sirait, Karina Romaliani & Muhammad Arsad Nasution & (Jurnal El-Thawalib, 2021)
As for the academic problem, it is wainting to know how checks and balances are in the Indonesian government system, whether checks and balances have been realized in the Indonesian government system. The purpose of this study is to determine the check and balance in the Indonesian government system in terms of Montesquei and the 1945 Constitution. The type of research used in this research is the type of normative research which collects data or scientific papers that are in accordance with the object of research pr collection of data in the form of literature (Library Research) or a study carried out to solve a problem which is basically based on critical and in depth study. Againts relevant library materials. The results of this study indicate that checks and balances in the Indonesian government are very important to avoid the concentration of power that can lead to arbitrariness, so it is necessary to share state power such as the Montesquei theory of trias politica and the 1945 Contitution also divides into three institutions of power but the 1945 Constitution explains that the Executive power is too large so that it can benefit anyone who holds the position of President. Check and balance in the Indonesian government system shows that it has not been fully implemented or materialized as seen from several cases raised in this thesis, namely the case of the KPK Bill, Perppu Number 1 of 2020 and the Omnibus Law Case Creation, there are still many discrepancies in stipulating the Bill, Perppu and the Law. So that in passing laws or stipulating the coordination between Executive, Legislative and Judiciary powers has not been well coordinated so that each bill or Perppu is not well systemized